Prevalence of Polypharmacy and Potentially Inappropriate Medications Use in Elderly Chinese Patients: A Systematic Review and Meta-Analysis - Tian, Fangyuan; Chen, Zhaoyan; Wu, Jinhui (Frontiers in Pharmacology, 2022)
Objectives: Polypharmacy and potentially inappropriate medications (PIMs) use among elderly Chinese patients have not yet been investigated by systematic review and meta-analysis. The purposes of this study were aimed to investigate the prevalence of polypharmacy and PIMs use and the risk factors associated with PIMs in elderly Chinese patients. Methods: Databases including PubMed, EMBase and Web of science were searched to collect studies with the Chinese criteria, Beers Criteria or STOPP criteria were used to evaluate the PIM status of elderly Chinese patients from inception to August 2021 (PROSPERO Code No: CRD42021262821). Observational studies reporting the prevalence of polypharmacy and PIMs use in elderly Chinese patients were meta-analyzed. Pooled prevalence and risk ratio (RR) with 95% confidence interval (CI) were calculated. Results: A total of 8 articles involving 4558786 patients were included. The overall prevalence of polypharmacy (concomitant use more than 5 medicines) and PIMs use pooled by meta-analysis in Chinese older patient was 48% (95% CI: 0.17, 0.79, P= 0.003) (inpatients 73%, outpatients 23%) and 39% (95% CI: 0.25, 0.54, P< 0.001) (inpatients 50%, outpatients 29%), respectively. The risk factors of PIM use were analyzed in the meta-analysis (particularly polypharmacy, gender, and older age), and polypharmacy, (RR: 2.03, 95% CI: 1.13, 3.64) was significantly associated with PIMs use. Conclusion: This meta-analysis demonstrated a high prevalence of polypharmacy and PIMs use among elderly patients in China. Affected by the quantity and quality of the included studies, the above conclusions need to be confirmed by large sample and high-quality studies.